The secret of the old clock - Keene, Carolyn; Tandy, Russell H. (Bedford, MA : Applewood Books ; Chester, CT : Distributed by Globe Pequot Press, 1991)
Nancy Drew's keen mind is tested when she searches for a missing will.
Keywords: Mystery and detective stories